Resident Wellness: An Intervention to Decrease Burnout and Increase Resiliency and Happiness - Rashi Aggarwal; Jill K. Deutsch; Jose Medina; Neil Kothari (Association of American Medical Colleges, 2017)
Introduction Despite the national focus on trainee burnout, effective wellness programs that can easily be incorporated into training curriculums are lacking. Strategies such as mindfulness and positive psychology, linked with deep breathing, have been shown to increase resiliency. We hypothesized that education about the neuroscience literature, coupled with teaching about well-being using short, easy-to-practice evidence-based exercises, would increase acceptance of this curriculum among residents and that providing protected time to practice these exercises would help trainees incorporate them into their daily lives. Methods Residents were asked to attend a 60-minute didactic featuring both the concepts and science behind well-being. Residents then attended 15-minute booster sessions during protected didactic time each week for a 12-week curriculum. The booster sessions were peer-led by wellness champions. Additionally, there were monthly competitions using free phone apps to promote physical fitness through steps and flights challenges. Results The 12-week curriculum was offered to 272 residents across five subspecialties of internal medicine, general surgery, anesthesiology, psychiatry, and physical medicine and rehabilitation. A total of 188 residents (69%) participated in the initial didactic component. The curriculum was positively received, with four of the five residency programs participating in weekly sessions. Residents in four participating departments then chose to continue the weekly sessions on a voluntary basis after the initial 12-week curriculum. Discussion It is feasible to implement a low-cost, peer-led wellness curriculum to educate residents and foster an environment during residency training where mindfulness, optimism, gratitude, and social connectedness are the norm.